Pancreatic fistulae after a pancreatico‐duodenectomy: are pancreatico‐gastrostomies safer than pancreatico‐jejunostomies? An expertise‐based trial and propensity‐score adjusted analysis. Issue 12 (19th June 2014) - Khalil, Jad Abou; Mayo, Nancy; Dumitra, Sinziana; Jamal, Mohammed; Chaudhury, Prosanto; Metrakos, Peter; Barkun, Jeffrey
Abstract: Background: A pancreatic fistula (PF) is a major contributor to morbidity and mortality after a pancreaticoduodenectomy (PD). There remains debate as to whether re‐establishing pancreaticoenteric continuity by a pancreatico‐gastrostomy (PG) can decrease the risk of a PF and complications compared with a pancreatico‐jejunostomy (PJ). The outcomes of patients undergoing these reconstructions after a PD were compared. Method: Patients undergoing a PD between 1999 and 2011 were selected from a prospective database and having undergone either a PG or PJ reconstruction. A propensity‐score adjusted multivariate logistic regression was performed to identify the effect of surgical technique on outcomes of PF, delayed gastric emptying (DGE) and total complications. Results: Twenty‐three out of 103 and 20 out of 103 ( P = 0.49) patients had PF and 74 out of 103 and 55 out of 103 patients had all‐grades DGE in the PG and PJ groups, respectively ( P = 0.02). The groups did not differ with regards to Clavien–Dindo grade of complications ( P = 0.29) but did differ with regards to the Comprehensive Complication Index (CCI) (38.4 versus 31.4 for PG versus PG, respectively, P = 0.02.) Propensity‐score adjusted multivariate analysis showed no effect of PG on PF ( P = 0.89), DGE grades B/C ( P = 0.9) or CCI ( P = 0.41). There remained an effect on all‐grades of DGE ( P = 0.012.) Discussion: Patients undergoing PG reconstruction had a similar rate of PF as those undergoing a PJ after a PD.